THU0292 Comparison of the Aecg Sjogren's Syndrome Classification Criteria to the Newly Proposed ACR Criteria in a Large, Carefully Characterized Sicca Cohort. (23rd January 2014) - Rasmussen, A.; Ice, J.; Li, H.; Grundahl, K.; Kelly, J.; Radfar, L.; Stone, D.; Hefner, K.; Anaya, J. M.; Rohrer, M.; Houston, G.; Lewis, D.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a complex disorder that is classically defined by autoimmune processes that result in exocrine gland dysfunction. There is no single clinical diagnostic test for SS, and for research purposes, multiple classification criteria have been proposed over the past decades; efforts to resolve discrepancies and weaknesses between the systems are ongoing. The most widely used criteria are the 2002 American-European Consensus Group (AECG) criteria; recently (2012), a new classification system has been proposed with provisional endorsement of the American College of Rheumatology (ACR). Objectives: To compare the performance of these two sets of criteria in a large carefully characterized sicca cohort. Methods: In a multidisciplinary clinic for the evaluation of sicca, we assessed features of salivary and lacrimal gland dysfunction and autoimmunity as defined by tests of both AECG and ACR criteria, classifying 646 participants. Global gene expression profiles were also compared in a subset of 180 participants. Results: Among the 646 subjects, 279 were classified as SS by AECG, 268 were so classified by ACR while 244 met both sets of criteria. The two sets of criteria were not significantly different (p=0.19; concordance=0.81); the ACR criteria had a sensitivity of 0.87 and specificity of 0.93. Thirty-five subjects were classified as SS by AECG only, of whom 26 (74%) had a salivary gland biopsy focal score >1, while 9 (26%) had positive anti-Ro/La. There were 24 ACR+/AECG-, who met ACR criteria mainly due to differences in the scoring of the corneal staining. All patients with SS, regardless of classification, had a similar gene expression profile, which was distinct from healthy controls. Conclusions: The two sets of classification criteria yield concordant results in the majority of cases and gene expression profiling suggests that patients meeting only one set of criteria are more similar to other SS subjects than to healthy controls. Thus, there is no clear evidence for increased value of the new criteria over the old from the data analysis or biological perspective. Moreover, the new criteria require evaluation in a specialty setting, while both the Schirmer's and WUSF tests can be performed in a standard medical office without the need for sophisticated equipment or specialists. This comparison shows that modifying classification using clinical criteria is not likely to lead to consequential improvements in our ability to identify patients with SS. We believe that such improvements in diagnostic acumen will require a more fundamental understanding of the pathogenic mechanisms than is at present available. Disclosure of Interest: None Declared